Teacher History Theses in Spain (1976-2020) - Sanchidrián-Blanco, María del Carmen; Álvarez-Jiménez, Victoria Eugenia; Molina Poveda, María Dolores (My University, 2025)
The aim of this research has been to find and analyze the theses on History of the Teaching Profession endorsed in Spain from 1976 (the year in which the TESEO database begins) until 2020. The Standing Working Group “Mapping of the discipline History of Education” (ISCHE36) and the historical-educational studies that we have carried out in Spain on doctoral theses have been used as a reference. First, a search was carried out for doctoral theses with the descriptor “History of Education” in the UNESCO thesaurus (1005 theses), refining the results with an analysis to determine which could be considered History of Education (860 theses). The results were then searched with word pairs in the title and abstract, such as “Master History*”. After refining the results, 177 more were found, for a total of 1037 theses. Next, a documentary analysis was done to determine which ones are on Teacher History, and 95 (almost 10%) were obtained. Teachers are one of the central elements of education, so studies with a historical perspective are in themselves a significant subject. We wanted to analyze four variables on the selected theses: the years in which they were defended, the gender of the authors, the universities where this subject has been most studied, and the dimensions that have been most studied. From the results obtained, it should be noted that the number of theses on this subject has been increasing over the decades, which is an indicator of its interest as a line of research. As for the dimensions of study within the History of the Teaching Profession, we have identified the following: a) theses on the initial training of teachers, especially from the study of specific institutions or in different places (cities, provinces, regions), highlighting among them those dedicated to teacher training colleges; b) the pedagogical thinking of teachers (biographies, pedagogical renewal movements, theoretical or methodological perspectives, etc.); c) theses based on teacher training in specific didactics (physical education, geography, mathematics, history, etc.); d) theses on the analysis of teachers, their working conditions and the teaching function; e) theses on the purge of teachers during the Franco dictatorship; f) theses with a gender perspective from the history of the education of women teachers; g) and theses on the continuing education of teachers. Therefore, we can say that the historical-educational theses about teachers, have been focused on their initial training (institutions and specific didactics, above all) and on primary education, with very few theses focused on other educational levels. There are also other lines to be highlighted, such as the evolution of teachers' thinking and working conditions. On the other hand, there are topics still not much studied in historical terms, such as the relationship between teachers and other educational agents (families, students themselves) or the differences in their training and professional practice between men and women. In short, this analysis offers us a field of study to analyze the changes and continuities of the teaching profession and its lines of research during the last decades.
Keywords: Educación - Historia - España - 1976-2020; Doctoral theses; History of Education; Teacher training; Higher education; Spain